Enhancing early childhood education student teachers' mentalization, interaction, and relationships: an online intervention - Marttila Jenny; Fukkink Ruben; Silvén Maarit (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Despite the growing importance of in-service teachers’ mentalization in early childhood education (ECE), studies on pre-service teachers are scarce. We embedded a newly developed version of video enhanced reflective practice (VERP) program in an online study module in a bachelor’s degree program to promote Finnish ECE student teachers’ interactional and relational competence via mentalization. The study module included evidence-based lectures and tutorials on children’s language development and teacher–child interactions, supplemented with multimedia material on a digital platform, independent work on assignments, and practical training. The VERP students’ (N = 21) and the trainers’ talk about cognition, but not about emotion, increased. The students rated their attuned interaction skills higher after the VERP training. After the study module, students perceived more closeness and less conflict in their overall relationships with children. The prospective ECE teachers appear to benefit from online mentalization training with complementary curricular content and teaching methods.